2019
DOI: 10.1080/10615806.2019.1623881
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty predicts analogue posttraumatic stress following adverse life events

Abstract: BACKGROUND AND OBJECTIVES: There is evidence that intolerance of uncertainty (IU) is associated with elevated post-traumatic stress (PTS) symptoms. There is a scarcity of research examining whether IU is prospectively related to PTS following exposure to negative life events. Using data from a Dutch student-sample, we examined the degree to which IU predicts post-traumatic stress symptoms associated with negative stressful life events (analogue posttraumatic stress (PTS)). DESIGN: This was a prospective survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Although IU has been proposed as a cognitive risk factor for generalized anxiety disorder, it is increasingly acknowledged as a transdiagnostic concept (McEvoy, Hyett, Shihata, Price, & Strachan, 2019 ). Failing to cope with uncertainty, individuals become more vulnerable to experience stress through life events and are at high risk of developing PTSS after various negative life events (Boelen, 2019 ; Oglesby, Boffa, Short, Raines, & Schmidt, 2016 ). Studies have also shown that IU is associated with insomnia (Voitsidis et al, 2020 ), less positivity (Bakioğlu, Korkmaz, & Ercan, 2020 ), fear of COVID-19 (Deniz, 2021 ), health anxiety (Tull et al, 2020 ), increased fear of the coronavirus (Mertens, Gerritsen, Duijndam, Salemink, & Engelhard, 2020 ), depression, and emotional eating (Pak, Süsen, Nazlıgül, & Griffiths, 2021 ), and can predict anxiety and depressive symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IU has been proposed as a cognitive risk factor for generalized anxiety disorder, it is increasingly acknowledged as a transdiagnostic concept (McEvoy, Hyett, Shihata, Price, & Strachan, 2019 ). Failing to cope with uncertainty, individuals become more vulnerable to experience stress through life events and are at high risk of developing PTSS after various negative life events (Boelen, 2019 ; Oglesby, Boffa, Short, Raines, & Schmidt, 2016 ). Studies have also shown that IU is associated with insomnia (Voitsidis et al, 2020 ), less positivity (Bakioğlu, Korkmaz, & Ercan, 2020 ), fear of COVID-19 (Deniz, 2021 ), health anxiety (Tull et al, 2020 ), increased fear of the coronavirus (Mertens, Gerritsen, Duijndam, Salemink, & Engelhard, 2020 ), depression, and emotional eating (Pak, Süsen, Nazlıgül, & Griffiths, 2021 ), and can predict anxiety and depressive symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that not only event-related stressors but also the individual differences in underlying psychological predispositions may affect how well individuals will cope or suffer in times of crises and traumatic exposures. The findings of the aforementioned studies indicated that IU, as a dispositional tendency, impairs the psychological functioning of the individual and predicts PTSS (Boelen, 2019 ; Oglesby et al, 2016 ), and the relationship between IU and PTSS is mediated by rumination (Taha et al, 2014 ). Longitudinal and experimental studies provided supporting evidence on the role of rumination in the development of PTSD symptoms, even after controlling for the initial level of stress symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that IU is fairly stable over time, though it can be modified with treatment ( Birrell et al, 2011 ; Mahoney & McEvoy, 2012 ). IU has also been shown to longitudinally predict mental health outcomes ( Boelen, 2019 ; Cai et al, 2020 ; Oglesby et al, 2016 ). Our findings add to the existing body of literature by confirming that IU is correlated with baseline depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma brings significant changes in many different aspects, and it is vital to assess stress in the face of a traumatic event (Uzer et al, 2020 ). Furthermore, stress is associated with other psychological problems such as uncertainty, anxiety, and poor emotional regulation (Boelen, 2019 ; Weiss et al, 2019 ). Stress among students is caused not only by academic issues, but by environmental and social factors (Raufelder et al, 2018 ).…”
Section: Student Distress During the Pandemicmentioning
confidence: 99%